mascRNA and its parent lncRNA MALAT1 promote proliferation and metastasis of hepatocellular carcinoma cells by activating ERK/MAPK signaling pathway - Xie, Shu-Juan (Cell Death Discov, 2021)
MALAT1-associated small cytoplasmic RNA (mascRNA) is a cytoplasmic tRNA-like small RNA derived from nucleus-located long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1). While MALAT1 was extensively studied and was found to function in multiple cellular processes, including tumorigenesis and tumor progression, the role of mascRNA was largely unknown. Here we show that mascRNA is upregulated in multiple cancer cell lines and hepatocellular carcinoma (HCC) clinical samples. Using HCC cells as model, we found that mascRNA and its parent lncRNA MALAT1 can both promote cell proliferation, migration, and invasion in vitro. Correspondingly, both of them can enhance the tumor growth in mice subcutaneous tumor model and can promote metastasis by tail intravenous injection of HCC cells. Furthermore, we revealed that mascRNA and MALAT1 can both activate ERK/MAPK signaling pathway, which regulates metastasis-related genes and may contribute to the aggressive phenotype of HCC cells. Our results indicate a coordination in function and mechanism of mascRNA and MALAT1 during development and progress of HCC, and provide a paradigm for deciphering tRNA-like structures and their parent transcripts in mammalian cells.